PEARLES challenges and solutions to the implementation of clinical research responses to epidemics and pandemics: a scoping review - Branagh Crealock-Ashurst; Shanthi Levanita; Sandrena Ruth Frischer; Sophia Adhikari; Winnie Mwebia; Zaharat Kadri-Alabi; Laura Davidson; Lisha Jeena; Megan Evans; Gabriella Morley; Eli Harriss; Gail Carson; et al. (EClinicalMedicine, 2025)
Summary: Conducting clinical research in response to infectious disease outbreaks presents unique challenges. In a previous review, we identified a range of political, economic, administrative, regulatory, logistical, ethical and social (PEARLES) challenges and proposed solutions to effective implementation of outbreak research responses. Following the COVID-19 pandemic, we conducted an update to explore if solutions recommended had been implemented, or new challenges identified. We searched seven databases (Ovid MEDLINE, Global Health, Embase, and PsycINFO, Scopus, Epistemonikos, Google Scholar) and grey literature from 01/06/2018 to 28/09/2023 for studies presenting PEARLES challenges/solutions to epi/pandemic research responses. Of 12,652 records, 191 were included. Our review identified many persisting challenges, particularly the lack of international research co-ordination, pre-planned research strategies, and limited research infrastructure in resource deprived settings. While some solutions were implemented, many remain recommendations e.g. pre-prepared regulatory guidelines and protocols, research infrastructure investment and international research coordination. Our data shows an urgent need to address challenges identified, implement and evaluate recommended solutions, to strengthen global health security to new and (re-) emerging epidemics and pandemics.